Perubahan Paradigma Pemasaran Konsep Tradisional vs Kontemporer - Al bait fiqri zulfikar sutarso; Abdillah Al Ghifari; Rohendi Rohendi (CV. Kalimasada Group, 2025)
This study aims to analyze the differences between traditional and contemporary marketing paradigms in modern business strategies. Traditional marketing focuses on one-way communication through conventional media such as television, radio, and newspapers, with the main goal of reaching a mass audience. In contrast, contemporary marketing emphasizes two-way communication, personalization, and the use of digital technologies such as social media, e-commerce, and data analytics. The research method employed is a literature review by examining relevant sources to compare strategies, communication channels, and long-term objectives of both paradigms. The findings reveal that traditional marketing remains relevant in certain contexts, particularly in building broad brand awareness, while contemporary marketing is superior in creating engagement and fostering customer loyalty. This study concludes that integrating traditional and contemporary paradigms provides a more effective strategy, as it enables companies to reach a wider audience while simultaneously building personal relationships with consumers.